Modeling and analysis of a hybrid boost DC-DC converter for distributed generation - V.Sudarsan, M; Saibabu, Ch; Satyanarayana, S (International Journal of Engineering and Technology, 2018)
As the power generating stations are located very far from the load centers, there is a necessity to transmit the power through the long transmission lines. The transmission efficiency and voltage profile are poor, due to the large amount of line losses and voltage drop. Thus to improve its performance, the generation of the power has to be done at the vicinity of load centers and is possible through the distributed generation (DG). The DG system consists of a boost converter which increases the dc input voltage obtained from an array of PV cells arranged on the solar panels.In this paper, the hybrid boost converter which is a high gain step-up dc-dc converter is modeled and analyzed for DG applications. The gain of this hybrid converter is D (duty ratio) times more than the normal boost converter and posses the advantages like less ripple current and high efficiency. Also the dynamic performance of the converters is compared in both open and closed loops from the simulation work carried out in MATLAB / Simulink environment.